Determining the mechanisms and priorities to achieve regularity in the shape of spaces of traditional housing in the city of Mosul - Al-Sanjary, Hasan Abdulrazzaq (Sulaimani Journal for Engineering Sciences, 2018)
Regularity in the shape of spaces in traditional house in the city of Mosul formed an important challenge for the designer, especially with the negative impact of the irregular shape of the dwelling and its limited area. This reinforces the assumption that there is a set of procedures adopted by the designer as mechanisms to achieve this characteristic in the dwelling spaces or to distribute the effect of irregularity between different spaces with priorities correspond to their functions performance efficiency. The research aims to identify the mechanisms adopted by the designer to achieve regularity and priorities for achieving between dwelling spaces (as an indicator of its relative importance and the efficiency of its containment of the living activities), and this gives us a clearer understanding of the spaces basic design and the way of living. To achieve this, a set of hypotheses were tested by measuring spaces regularity of a sample of traditional houses in Mosul , to design the mechanisms used to achieve regularity and its priorities between different house spaces , and the relevance of these mechanisms and priorities with the affect of the shape characteristics of house plot or the spaces characteristics , activities and its spatial organization in the dwelling.
Keywords: Regularity in architecture; Traditional house; House spaces